Gummatous cutaneous tuberculosis associated with the use of infliximab for Crohn's disease, - Lucas Campos Garcia; Everton Carlos Siviero do Vale; Maria de Lourdes Ferrari; Lauro Damasceno de Carvalho Faria (Sociedade Brasileira de Dermatologia, 2021)
Abstract As the treatment of infectious and parasitic diseases improved, the prevalence of these conditions declined. However, with the expansion of the use of immunobiologicals, opportunistic infections have emerged, especially under atypical presentations. The present study reports the case of a patient treated with infliximab for Crohn's disease, who presented diarrhea, weight loss, abdominal pain, fever, and subcutaneous erythematous nodules that evolved with spontaneous fluctuation and ulceration. With the finding of alcohol-resistant bacilli and Mycobacterium tuberculosis DNA in a cutaneous fragment, through polymerase chain reaction, the diagnosis of gummatous tuberculosis was confirmed, probably secondary to hematogenous dissemination from an intestinal focus.